Strategi Pengembangan Kinerja Penyuluh Pertanian dalam Pendidikan Jarak Jauh Universitas Terbuka: Kasus Alumni UT di wilayah Serang, Karawang, Cirebon, dan Tanggamus - Nurul Huda; Sumardjo Sumardjo; Margono Slamet; Prabowo Tjitropranoto (Jurnal Penyuluhan, 2010)
Performance is an implementation of work. For agricultural extension agents, performances are indicators of how well they do the job. The objectives of this research were to determine the level of performances of agricultural extention agent and factors affecting them. Data were collected in July through December 2008. A survey technique was implemented among 111 agricultural extension agents who were graduated from UT and among 88 farmers in four different locations, namely Serang, Karawang, Cirebon, and Tanggamus. By using In depth interview, a qualitative information were also used in order to elaborate the findings. Data was analyzed by using descriptive and path analysis. The findings indicated that UT’s graduates had a high level in performances. Several dominant factors influenced their performances. This study suggests several strategies to increase the performances of agricultural extension agents.(Keywords: agricultural extension agents, performances, distance education).